Software system development to calculate electro-optical characteristics of organic light-emitting structures - Готра, Зенон Юрійович; Іванюк, Христина Богданівна; Чапран, Мар’ян Мирославович; Білас, Орест Євгенович; Маланчук, Орест Андрійович (Eastern-European Journal of Enterprise Technologies, 2015)
The current state of development of organic electronics was analyzed in the paper. The problem of elaborating low-cost express measurements of chromatic and luminance characteristics as an alternative to costly, located in specialized laboratories was considered. Methodology for determining the chromatic characteristics of organic light-emitting diodes (OLED), adapted to planar light-emitting structures was developed. The software to calculate the basic electro-optical characteristics of OLED, namely chromatic, luminance and current-voltage characteristics of organic light-emitting diodes according to the previously developed calculation methodology was designed. The developed software solves the problem of cumbersome calculations of basic electro-optical characteristics of OLED, it is adapted to a modern operating system, provides calculation correctness and accuracy, easy interface to effectively solve the computational problem for the platform.